2020
DOI: 10.1016/j.phrs.2020.105126
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Huoxiang Zhengqi dropping pills and Lianhua Qingwen granules in treatment of COVID-19: A randomized controlled trial

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
220
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(222 citation statements)
references
References 7 publications
0
220
0
2
Order By: Relevance
“…Currently, some commercial Chinese medicine preparations are also used in this epidemic. A randomized clinical trial evaluated the clinical efficacy of Huoxiang Zhengqi drop pills and/or Lianhua Qingwen granules combined with Western medicine in treating COVID-19 [ 245 ]. The results showed that Huoxiang Zhengqi drop pills combined with Lianhua Qingwen granules and Western medicine had advantages in improving nausea, vomiting, and sore limbs, as well as reducing the use of antibiotics.…”
Section: Understanding Covid-19 From the Perspective Of Tcmmentioning
confidence: 99%
“…Currently, some commercial Chinese medicine preparations are also used in this epidemic. A randomized clinical trial evaluated the clinical efficacy of Huoxiang Zhengqi drop pills and/or Lianhua Qingwen granules combined with Western medicine in treating COVID-19 [ 245 ]. The results showed that Huoxiang Zhengqi drop pills combined with Lianhua Qingwen granules and Western medicine had advantages in improving nausea, vomiting, and sore limbs, as well as reducing the use of antibiotics.…”
Section: Understanding Covid-19 From the Perspective Of Tcmmentioning
confidence: 99%
“…In vitro: influenza virus A1/Qianfang/166/85 (H1N1) in A549 10, 5, 2.5, 1.25, 0.63 mg/ml Wang et al, 2008;Dong et al, 2015;Wang et al, 2016 In TNF-a, IP-10, and MCP-1, and also inhibits SARS-CoV-2 replication in Vero E6 cells and markedly reduced proinflammatory cytokines (TNF-a, IL-6, CCL-2/ MCP-1 and CXCL-10/IP-10) production at the mRNA levels. Zhu et al, 2003;Ding et al, 2017;Guan et al, 2018;Bao et al, 2019;Gao et al, 2020;Li R. F. et al, 2020;Xiao et al, 2020 In Prospective study: patients with severe acute respiratory syndrome (SARS) in the mild or severe stage. Prospective study: patients with severe acute respiratory 0.755 g/ml, 400 ml/day Glucocorticoid, ganciclovir, levofloxacin, and invigorate blood, boost qi and nourish yin, relieve cough and calm panting, Formula III for SARS during Convalescence (Feidian Huifuqi Sanhao Fang) with recovery to boost qi and nourish yin, fortify the spleen and harmonize the stomach.…”
Section: Granular Solutionmentioning
confidence: 99%
“…Hanshiyi Formula, a TCM prescription, can significantly reduce the progression to severe disease in patients with mild and moderate COVID-19, which may both prevent and treat the disease [5] . The use of Huoxiang Zhengqi Pill and Lianhua Qingwen Granule combined with Western medicine may have advantages for COVID-19 patients in improving clinical symptoms, reducing utilization rate of antibacterial and antiviral drugs, and improving patient prognosis [6] . Furthermore, TCM has shown rapid clinical improvements.…”
Section: Introductionmentioning
confidence: 99%